Stop-gain mutations in UBAP1 cause pure autosomal-dominant spastic paraplegia - Lin, Xiang; Su, Hui-Zhen; Dong, En-Lin; Lin, Xiao-Hong; Zhao, Miao; Yang, Can; Wang, Chong; Wang, Jie; Chen, Yi-Jun; Yu, Hongjie; Xu, Jianfeng; Ma, Li-Xiang; et al. (Brain (London, England : 1878), 2019)
Hereditary spastic paraplegias refer to a heterogeneous group of neurodegenerative disorders resulting from degeneration of the corticospinal tract. Clinical characterization of patients with hereditary spastic paraplegias represents progressive spasticity, exaggerated reflexes and muscular weakness. Here, to expand on the increasingly broad pools of previously unknown hereditary spastic paraplegia causative genes and subtypes, we performed whole exome sequencing for six affected and two unaffected individuals from two unrelated Chinese families with an autosomal dominant hereditary spastic paraplegia and lacking mutations in known hereditary spastic paraplegia implicated genes. The exome sequencing revealed two stop-gain mutations, c.247_248insGTGAATTC (p.I83Sfs*11) and c.526G>T (p.E176*), in the ubiquitin-associated protein 1 (UBAP1) gene, which co-segregated with the spastic paraplegia. We also identified two UBAP1 frameshift mutations, c.324_325delCA (p.H108Qfs*10) and c.425_426delAG (p.K143Sfs*15), in two unrelated families from an additional 38 Chinese pedigrees with autosomal dominant hereditary spastic paraplegias and lacking mutations in known causative genes. The primary disease presentation was a pure lower limb predominant spastic paraplegia. In vivo downregulation of Ubap1 in zebrafish causes abnormal organismal morphology, inhibited motor neuron outgrowth, decreased mobility, and shorter lifespan. UBAP1 is incorporated into endosomal sorting complexes required for transport complex I and binds ubiquitin to function in endosome sorting. Patient-derived truncated form(s) of UBAP1 cause aberrant endosome clustering, pronounced endosome enlargement, and cytoplasmic accumulation of ubiquitinated proteins in HeLa cells and wild-type mouse cortical neuron cultures. Biochemical and immunocytochemical experiments in cultured cortical neurons derived from transgenic Ubap1flox mice confirmed that disruption of UBAP1 leads to dysregulation of both early endosome processing and ubiquitinated protein sorting. Strikingly, deletion of Ubap1 promotes neurodegeneration, potentially mediated by apoptosis. Our study provides genetic and biochemical evidence that mutations in UBAP1 can cause pure autosomal dominant spastic paraplegia.